2021
DOI: 10.21203/rs.3.rs-42816/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcriptome regulation of carotenoids in five flesh-colored watermelon (Citrullus lanatus)

Abstract: Background: Fruit flesh color in watermelon (Citrullus lanatus) is a great index for evaluation of the appearance quality and a key contributor influencing consumers' preferences, but the molecular mechanism of this intricate trait remain largely unknown. Here, the carotenoids and transcriptome dynamics during the fruit development of cultivated watermelon with five different flesh colors were analyzed.Results: A total of 13 carotenoids and 16781 differentially expressed genes (DEGs) including 1295 transcripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 52 publications
(91 reference statements)
0
2
0
Order By: Relevance
“…KEGG enrichment analysis and NR annotation showed that, there are 27 structural genes participated in carotenoid metabolic pathway among the four combinations (LY vs. W, Y vs. W, O vs. W, OR vs. W), and the sweetpotato carotenoid metabolic pathway were mapped (Figure 3). The pathway was constructed based on KEGG and references (Suematsu et al, 2020;Xu et al, 2021;Yuan et al, 2021;KEGG, 2022). Of which 10 DEGs namely Or (1), CRTISO (1), CYP97B2 (1), CHYB (1), ZEP (2), NSY (1) and DWARF27 (3) were playing major role in carotenoid biosynthesis pathway and 17 DEGs namely CCD1 (8), CCD4 (1), CCD7 (1), NCED (4) and CYP707A (3) were related to carotenoid degradation pathway.…”
Section: Degs Involved In Carotenoid Metabolic Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…KEGG enrichment analysis and NR annotation showed that, there are 27 structural genes participated in carotenoid metabolic pathway among the four combinations (LY vs. W, Y vs. W, O vs. W, OR vs. W), and the sweetpotato carotenoid metabolic pathway were mapped (Figure 3). The pathway was constructed based on KEGG and references (Suematsu et al, 2020;Xu et al, 2021;Yuan et al, 2021;KEGG, 2022). Of which 10 DEGs namely Or (1), CRTISO (1), CYP97B2 (1), CHYB (1), ZEP (2), NSY (1) and DWARF27 (3) were playing major role in carotenoid biosynthesis pathway and 17 DEGs namely CCD1 (8), CCD4 (1), CCD7 (1), NCED (4) and CYP707A (3) were related to carotenoid degradation pathway.…”
Section: Degs Involved In Carotenoid Metabolic Pathwaymentioning
confidence: 99%
“…In recent years, several transcription factors that regulate and control the carotenoid metabolic pathway have been identified in several crop species (Ampomah-Dwamena et al, 2019;Yuan et al, 2021). In present study, we performed WGCNA to identify transcription factors that coordinately regulate the biosynthesis and accumulation of carotenoids.…”
Section: Transcription Factor Related To Carotenoid Metabolic Pathway...mentioning
confidence: 99%